On the Issue of Labor Relations Discontinuance by Staff Reduction - A. A. Sheveleva (Сибирское юридическое обозрение, 2012)
This article is devoted to consideration of issues related to the procedure of labor law contract termination by staff reduction. The author, analyzing the judicial practice, gives practical recommendations on the procedure of employment relationships discontinuance.